Heavy metals monitoring in mussels Mytilus galloprovincialis from the Apulian coasts (Southern Italy) - SPADA, L.; ANNICCHIARICO, C.; CARDELLICCHIO, N.; GIANDOMENICO, S.; DI LEO, A. (Mediterranean Marine Science, 2013)
Concentrations of six heavy metals (Cd, Cr, Cu, Hg, Pb and Zn) and one semi-metal (As) were determined in tissues of mussels Mytilus galloprovincialis collected along the Apulian coasts (Mediterranean sea). This project, performed in 2009, was targeted toward the assessment of levels and spatial distribution of metals in the environment in order to evaluate the coastal water quality using mussels as bioindicators and health risk for mussel consumers.The concentrations (mg/kg d.w.) of these metals ranged from 6.35 to 76.17 for arsenic (As), 0.38 to 2.54 for cadmium (Cd), 0.96 to 9.46 for chromium (Cr), 5.26 to 19.22 for copper (Cu), 0.10 to 0.81 for mercury (Hg), 25.00 to 110.51 for zinc (Zn) and from 0.37 to 3.25 for lead (Pb). These levels were lower than the permissible limits set by European Commission and FAO with the exception for Cr in three sampling stations. Evaluation of the risk associated to molluscs consumption for human health suggested that there is no evident risk for a moderate Mytilus g. consumer, however heavy metals concentrations must be monitored periodically and carefully with respect to the consumers health.